Identifying gp85- regions involved in Epstein- Barr virus binding to Blymphocytes. (2004)
Epstein–Barr virus lacking glycoprotein gp85 cannot infect B-cells and epithelial cells. The gp85 belongs to the molecular complex required for virus invasion of B-lymphocyte or epithelial cells. Moreover, there is evidence that gp85 is necessary for virus attachment to epithelial cells. Thirty-six peptides from the entire gp85-sequence were tested in epithelial and lymphoblastoid cell line binding assays to identify gp85-regions involved in virus–cell interaction. Five of these peptides presented high binding activity to Raji, Ramos, P3HR-1, and HeLa cells, but not to erythrocytes; Raji-cell affinity constants were between 80 and 140 nM. Of these five peptides, 11435 (181TYKRVTEKGDEHVLSLVFGK200), 11436 (201TKDLPDLRGPFSYPSLTSAQ220), and 11438 (241YFVPNLKDMFSRAVTMTAAS260) bound to a 65 kDa protein on Raji-cell surface. These peptides and antibodies induced by them (recognising live EBV-infected cells) inhibited Epstein–Barr virus interaction with cord blood lymphocytes. It is thus probable that gp85-regions defined by peptides 11435, 11436, and 11438 are involved in EBV invasion of B-lymphocytes.